Gesture Use and Processing: A Review on Individual Differences in Cognitive Resources - Özer, Demet; Göksun, Tilbe (Frontiers in Psychology, 2020)
Speakers use spontaneous hand gestures as they speak or think. These gestures serve many functions for speakers who produce them as well as for listeners who observe them. To date, studies in gesture literature mostly focused on group-comparisons or the external sources of variation to examine when people use, process, and benefit from using and observing gestures. However, there are also internal sources of variation in gesture use and processing. People differ in how frequently they use gestures, how salient their gestures are, for what purposes they produce gestures, and how much they benefit from using and seeing gestures during comprehension and learning depending on their cognitive dispositions. This review addresses how individual differences in different cognitive skills relate to how people employ gestures in production and comprehension across different ages (from infancy through adulthood to healthy aging) from a functionalist perspective. We conclude that speakers and listeners can use gestures as a compensation tool during communication and thinking that interact with individuals’ cognitive dispositions.